Statin-induced Myopathy - Dalby, Anthony J. (SA Heart Journal, 2017)
Atherosclerotic cardiovascular disease (ASCVD) is the leading cause of death worldwide. HMGCoA reductase inhibitors or “statins” reduce low density lipoprotein cholesterol and reduce the risks of myocardial infarction, stroke and death in the presence of dyslipidaemia. In consequence, statins are prescribed to a large number of patients requiring primary or secondary prevention. A variety of side-effects may arise during the course of statin treatment which interfere with the quality of patients’ lives and reduce their compliance with therapy. Muscle symptoms constitute the most common of these side-effects and are the most frequent reason for discontinuing treatment. This review defi nes the muscle, tendon and joint disorders encountered by patients on statin treatment, their possible relationship to statin use, and the factors that facilitate the emergence of symptoms. The subtypes of statin myopathy are discussed and a general defi nition of statin myopathy is offered. Expert advice on managing statin myopathy is summarised.